2011
DOI: 10.1038/ijir.2011.28
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial apoptosis decrease following tadalafil administration in patients with arterial ED does not last after its discontinuation

Abstract: Although it is well known that phosphodiesterase V inhibitors, used to treat patients with ED, can improve the endothelial dysfunction in organic vascular forms, few studies have explored the duration of their effect on the endothelium after discontinuation. Therefore, the purpose of this study was to evaluate the serum concentrations of apoptotic endothelial microparticles (EMPa), selected as a marker of endothelial damage, in patients with arterial ED at baseline, during tadalafil administration and 3 and 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…We have also shown that administration of sildenafil induces vasodilation in forearm circulation, and increases both the ACh‐induced and SNP‐induced vasodilation in both smokers and non‐smokers; that sildenafil increases the ratio of ACh‐induced vasodilation to the ratio of SNP‐induced vasodilation; and that the NOS inhibitor l ‐NMMA diminishes the augmentation of ACh‐induced vasodilation after administration of sildenafil, suggesting that inhibition of PDE5 increases NO‐induced vasodilation . The effects of PDE5 inhibitors on endothelial function in patients with ED/LUTS/BPH are summarized in Table . These findings suggest that the mechanism by which PDE5 inhibitors augment or improve vascular function, including endothelial function and vascular smooth muscle function, is mainly activation of the eNOS–NO–cGMP pathway.…”
Section: Pde5 and Vascular Functionmentioning
confidence: 75%
See 1 more Smart Citation
“…We have also shown that administration of sildenafil induces vasodilation in forearm circulation, and increases both the ACh‐induced and SNP‐induced vasodilation in both smokers and non‐smokers; that sildenafil increases the ratio of ACh‐induced vasodilation to the ratio of SNP‐induced vasodilation; and that the NOS inhibitor l ‐NMMA diminishes the augmentation of ACh‐induced vasodilation after administration of sildenafil, suggesting that inhibition of PDE5 increases NO‐induced vasodilation . The effects of PDE5 inhibitors on endothelial function in patients with ED/LUTS/BPH are summarized in Table . These findings suggest that the mechanism by which PDE5 inhibitors augment or improve vascular function, including endothelial function and vascular smooth muscle function, is mainly activation of the eNOS–NO–cGMP pathway.…”
Section: Pde5 and Vascular Functionmentioning
confidence: 75%
“…reported that tadalafil improved FMD, increased plasma levels of nitrite/nitrate and decreased plasma levels of endothelin‐1, a vasoconstrictor, in ED patients with atherosclerosis . It has also been shown that inhibition of PDE5 increases the number of endothelial progenitor cells and circulating progenitor cells, and decreases serum levels of endothelial microparticles, a marker of endothelial cell apoptosis, in patients with ED . Recently, Fukumoro et al .…”
Section: Pde5 and Vascular Functionmentioning
confidence: 96%
“…In contrast, some studies had negative findings for durability. Although administration of tadalafil decreased the serum endothelial microparticle concentration, which was selected as a marker of endothelial damage, in patients with arterial ED, this positive effect on endothelial dysfunction disappeared 6 months after tadalafil discontinuation [64]. Following discontinuation of tadalafil after a 1-year open-label extension, the mean IIEF-EF score declined markedly to near baseline levels [24].…”
Section: Advantages Of Chronic Pde5 Inhibitor Use In Men With Edmentioning
confidence: 99%
“…Moreover, we previously reported the diagnostic value of this EPC and EMP phenotype in other categories of patients with aED, such as those with associated late onset hypogonadism or metabolic syndrome. In addition, we evaluated the effects of androgen replacement therapy, aerobic physical activity, and tadalafil administration on these markers (La Vignera, 2011; La Vignera et al, 2011a,b,c,d; 2012a,c,d). Finally, we have previously shown that a more generalized peripheral atherosclerotic process is associated with a more severe penile artery insufficiency (Vicari et al, 2006); therefore, patients with aED should undergo an extensive echo‐duplex examination (Vicari et al, 2006).…”
mentioning
confidence: 99%